Studies on size distribution and health risk of 37 species of polycyclic aromatic hydrocarbons associated with fine particulate matter collected in the atmosphere of a suburban area of Shanghai city, China. (July 2016) - Wang, Qingyue; Kobayashi, Keisuke; Lu, Senlin; Nakajima, Daisuke; Wang, Weiqian; Zhang, Wenchao; Sekiguchi, Kazuhiko; Terasaki, Masanori
Abstract: Polycyclic aromatic hydrocarbons (PAHs) in suspended particulate matter (SPM) contribute significantly to health risk. Our objectives were to assess the size distribution and sources of 26 PAHs and 11 polycyclic aromatic compounds (PACs) in SPM in the suburban area, Shanghai city, China. Air sampling was carried out on the rooftop of a five-stories building in the campus of Shanghai University. An Andersen high-volume air sampler was employed to collect ambient size-segregated particles from August to September 2015. The toxic particulate PAHs were determined by the gas chromatography mass spectrometry. The concentrations of total PAHs (TPAHs) in SPM and PM1.1 (suspended particulate matter below 1.1 μm) were in the ranges of 4.58–14.5 ng m −3 and 1.82–8.56 ng m −3, respectively. 1, 8-naphthalic anhydride showed the highest concentrations among 37 species of PAHs and PACs ranging 7.76–47.9 ng m −3 and 1.50–17.6 ng m −3 in SPM and PM1.1, respectively. The concentrations of high molecular weight 5–6 ring PAHs followed a nearly unimodal size distribution with the highest peak in PM1.1, while other lower molecular weight PAHs were not dependent on particle sizes. The toxicity analysis indicated that the carcinogenic potency of particulate PAHs primarily existed in PM1.1 . Regarding meteorological parameters and other pollutants, the positive effect of humidity and NO2 over PAHs was confirmed. Diagnostic ration indicated that the particulate PAHs in Shanghai were mainly derived from motor-vehicle or petroleum combustion. The highest benzo[ a ]pyrene equivalent (BaPeq) in SPM and PM1.1 were 2.15 ng m −3 and 1.43 ng m −3 calculated by the toxicity equivalency factor, and 69.31 ng m −3 and 47.81 ng m −3 estimated by the potency equivalency factors, respectively. The highest contributors in the total carcinogenicity of the particulate PAHs were dibenzo[ a, h ]pyrene (46.2% and 45.0%) and benz[ j ]aceanthrylene (80.2% and 83.1%), respectively while benzo[ a ]pyrene is lower contributor than other carcinogenic PAHs. Graphical abstract: Highlights: 37 particulate polycyclic aromatic hydrocarbons (PAHs) in summer of Shanghai, China. The highest concentration of 1, 8-naphthalic anhydride among 37 species of PAHs. The dominant PAHs from vehicular sources even in the suburban of Shanghai city. The higher carcinogenic potency of PAHs in fine particles below 1.1 μm.